2006
DOI: 10.1111/j.1365-2842.2006.01542.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental implants in patients with bruxing habits

Abstract: Bruxism (teeth grinding and clenching) is generally considered a contraindication for dental implants, although the evidence for this is usually based on clinical experience only. So far, studies to the possible cause-and-effect relationship between bruxism and implant failure do not yield consistent and specific outcomes. This is partly because of the large variation in the literature in terms of both the technical aspects and the biological aspects of the study material. Although there is still no proof for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(133 citation statements)
references
References 35 publications
2
124
1
6
Order By: Relevance
“…In accordance with the literature review conducted by Lobbezoo et al 8 , bruxism is generally considered a contraindication for the installation of dental implants. Due to the fact that possible causal relations between bruxism and implant failure lack specific and consistent results, this study urges professionals to use a clinical guide when attending patients with bruxism.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In accordance with the literature review conducted by Lobbezoo et al 8 , bruxism is generally considered a contraindication for the installation of dental implants. Due to the fact that possible causal relations between bruxism and implant failure lack specific and consistent results, this study urges professionals to use a clinical guide when attending patients with bruxism.…”
Section: Discussionsupporting
confidence: 64%
“…They are considered harmful to the stomatognathic system 7 , and their effects depend on the magnitude and direction of the forces 8 . Naert et al 9 have indicated that overload caused by parafunctional habits is the most likely cause of dental implant and marginal bone tissue loss.…”
Section: Introductionmentioning
confidence: 99%
“…24 Excessive loading has been associated with non axial forces, cantilevers, parafunction and increased implantabutment ratios. 25,26,27 Mechanical complications have also been associated with the inappropriate selection or use of materials, manufacturing imperfections, ill-fitting frameworks and trauma. 3,28,29 In partially edentulous patients implant supported prostheses should be designed so that they allow light occlusal contact in the intercuspal position.…”
Section: Mechanical Complicationsmentioning
confidence: 99%
“…24,27 Following treatment, hard nocturnal splints have been advocated to reduce the incidence of mechanical complications. 25 However, these are only likely to be effective if patient compliance is good. Frameworks should be constructed from appropriate materials, be of adequate thickness and designed appropriately to support the veneering material which may be porcelain, acrylic or composite resin.…”
Section: Mechanical Complicationsmentioning
confidence: 99%
“…Bruxism is also said to have some amount of effect on the success of implant-supported prosthesis. 6 Hence, we aimed for the present study to assess the incidence of prosthetic complications in patients rehabilitated with implant-borne prosthesis in a sleep disorder unit.…”
Section: /Jp-journals-10024-2133mentioning
confidence: 99%